The Legal Basis for Considering the Corona Pandemic a Force majeure "A Comparative Analytical Study" - Aqeel Abdulhussein Alkhateeb , Zahraa; AbdulQader Maaroof , Prof.Dr. Hussein (Basra studies journal, 2022)
The force majeure theory emerged as a legal adaptation of the Corona pandemic to address the disruption caused by the pandemic in the work of the courts. Besides, the failure of the opponents to perform the procedural work in the time specified for it in the law, as a result of the seriousness of the pandemic and its repercussions, which prompted governments to impose many restrictions that limit the freedoms of individuals. Notably, the most important of which is the general curfew, and on the other hand, a person may be exposed to this epidemic in a way that prevents him from normal movement. And, the effects of the disease and its complications are severe. Thus, he loses his eligibility for litigation and he is unable to assign someone to represent him, and accordingly the ban or injury affects the person’s ability to carry out the procedural work normally. Consequently, it is impossible for the opponent to go to court because of the curfew, or because he is infected with this epidemic.